Extraction of cellulose from rice husk, durian husk and pineapple peels using acid and alkaline pre-treatment with bleaching process - Sheryll Sherllyn Sim (2024)
Cellulose is a crucial fiber polymer that gives plants strength and high resistance to stretching, making it vital in industries such as paper, textiles, and biofuels. The material's hydrophobic properties provide excellent durability and solvent resistance, leading to prolonged performance. The aim is to extract cellulose from agricultural byproducts such as pineapple peels, rice husks, and durian husks using alkaline pretreatment and bleaching techniques to enhance purity. The extracted cellulose will undergo comprehensive analysis utilizing SEM, FTIR, XRD, and TGA. This thorough evaluation seeks to analyze cellulose samples' microstructural, chemical, and thermal properties to enhance understanding of their potential commercial applications. Extracting cellulose from rice, durian, and pineapple peels includes a practical alkaline pretreatment approach using sodium or potassium hydroxide, followed by bleaching with chlorine dioxide or hydrogen peroxide. RH 1 and PP 1 had the highest cellulose percentages at 75% and 74%, respectively, followed by DH 1 at 70%, DH 2 at 66%, and PP 2 at 66%. The samples analyzed indicated that the alkaline treatment substantially boosted the cellulose content by eliminating hemicellulose, lignin, and other impurities. During a study on cellulose sources, the pineapple peel was determined to be the most efficient compared to rice husk and durian husk. Its reduced processing time and the generation of a translucent residue revealed a superior conclusion in cellulose extraction. This study aids in identifying agricultural byproducts that can be used as cellulose sources to create biodegradable microbeads in the future.